2023
DOI: 10.3847/1538-4357/acccea
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA Survey of 70 μm Dark High-mass Clumps in Early Stages (ASHES). IX. Physical Properties and Spatial Distribution of Cores in IRDCs

Abstract: The initial conditions found in infrared dark clouds (IRDCs) provide insights on how high-mass stars and stellar clusters form. We have conducted high-angular resolution and high-sensitivity observations toward thirty-nine massive IRDC clumps, which have been mosaicked using the 12 and 7 m arrays from the Atacama Large Millimeter/submillimeter Array. The targets are 70 μm dark massive (220–4900 M ⊙), dense (>104 cm−3), and cold (∼10–20 K) clumps located at distances between 2 and 6 kpc. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 105 publications
(168 reference statements)
4
35
0
Order By: Relevance
“…HFSs have been the focus of several statistical studies (Kumar et al 2020;Zhou et al 2022;Liu et al 2023). In particular, Liu et al (2023) studied a sample of 17 HFSs composed of two distinct evolutionary stages using high-angular resolution (∼1″-2″) Atacama Large Millimeter/submillimeter Array (ALMA) 1.3 mm (Li et al 2023;Morii et al 2023) and 3 mm continuum data (Liu et al 2020b;Sanhueza et al 2019). Liu et al (2023) discuss the observed trend on multi-scales (i.e., clumps and cores) of increasing mass and mass surface density with the evolution from IR-dark to IR-bright stage, the mass-segregated cluster of young stellar objects, and the potentially preferential escape directions of outflow feedback.…”
Section: Multi-scale Scenario Of High-mass Star Formationmentioning
confidence: 99%
“…HFSs have been the focus of several statistical studies (Kumar et al 2020;Zhou et al 2022;Liu et al 2023). In particular, Liu et al (2023) studied a sample of 17 HFSs composed of two distinct evolutionary stages using high-angular resolution (∼1″-2″) Atacama Large Millimeter/submillimeter Array (ALMA) 1.3 mm (Li et al 2023;Morii et al 2023) and 3 mm continuum data (Liu et al 2020b;Sanhueza et al 2019). Liu et al (2023) discuss the observed trend on multi-scales (i.e., clumps and cores) of increasing mass and mass surface density with the evolution from IR-dark to IR-bright stage, the mass-segregated cluster of young stellar objects, and the potentially preferential escape directions of outflow feedback.…”
Section: Multi-scale Scenario Of High-mass Star Formationmentioning
confidence: 99%
“…Likewise, we find no argument from this analysis supporting a more isolated, monolithic-type formation for the more-massive YSOs. An explanation for these results could be that mass segregation happens at later stages of cluster lifetimes (Della Croce et al 2023;Farias & Tan 2023), and that cluster properties at early stages are determined by the initial cloud size and mass, and not the stellar content (Farias & Tan 2023;Morii et al 2023). It is also an option that the YSOs considered in this work are not the most-massive YSOs in several of the detected clusters, which might contain heavily embedded massive YSOs that escaped the Gaia survey.…”
Section: Cluster Properties Of Ysos Of Different Stellar Massesmentioning
confidence: 86%
“…The larger core mass in the fragments demands either additional support from turbulence and magnetic fields (Wang et al 2012) or a continuous accretion onto the core (Vázquez-Semadeni et al 2023). On the other hand, observations also find that the mass of these cores does not contain sufficient material to form a massive star (Sanhueza et al 2017(Sanhueza et al , 2019Morii et al 2023), and the cores typically continue to fragment when observed at higher angular resolution (Wang et al 2011(Wang et al , 2014Zhang et al 2015;Olguin et al 2021Olguin et al , 2022, or at slightly later evolutionary stages (e.g., Palau et al 2015;Beuther et al 2018). Therefore, the idea of monolithic collapse (McKee & Tan 2003) for massive star formation does not match the observations.…”
Section: Introductionmentioning
confidence: 94%
“…Such a continuous mass accretion is observed directly (Dewangan et al 2022;Redaelli et al 2022;Xu et al 2023a) or indirectly (Contreras et al 2018). More recent observations of IRDCs with the Atacama Large Millimeter/submillimeter Array (ALMA) routinely reach a mass sensitivity far below the thermal Jeans mass and detect a large population of low-mass cores in the clumps that are compatible with the thermal Jeans mass (Sanhueza et al 2019;Svoboda et al 2019;Morii et al 2023). These cores may form low-mass stars in a cluster.…”
Section: Introductionmentioning
confidence: 99%